The informal formal and its role in Enhancing the communicative discourse of the printed achievement (Journal of the College of Basic Education, 2022)
The use of the new, innovative and strange compound (unfamiliar) by borrowing the forms from their familiar framework by assembling the various elements in another context to obtain this new and employing it in the printing achievements and the advertising poster is one of these achievements as it is a means of mass communication with its intellectual contents with predetermined goals. Contributes to the delivery of many technical design and display methods that have proven their usefulness over time in creating the appropriate impact on the recipient, and by showing the researcher a set of printed models and then observing observations represented by the following question